Exploring Secondary School Performance by Using Machine Learning Algorithms - Felicia; Ferren (Journal of Educational Analytics, 2022)
Education is an important factor to achieve a better life and to help the economy. There are lots of levels of education and the education level that we will analyze is secondary education. Secondary education provides lots of benefits, starting from knowledge and skills, training in attitudes, instincts, and ensuring students will get a job after graduating. Not only that, but Portuguese secondary education also guides the development of the students so they will be well prepared for work and real-life situations. The educational level of Portuguese has also improved from last decades because in the past, lots of students failed and this causing failure rates is increasing. The failures are caused by Mathematics which are the core subjects. Because of this, Portuguese schools are still monitoring students who didn’t pass yet by using the data. We will analyze using 3 operators (i.e. Generalized Linear Model , Random Forest, Naive Bayes) and found out that past grades, demographic, and several attributes play a role in education (Cortez & Silva, 2008). We also found that Naive Bayes method has a high accuracy. The goal of these projects is to identify what makes education successful and fail and to aim for any new prediction.